An Analysis of English for Specific Purposes Textbook Entitled Intelligent Bussines Based on Cunningsworth's Theory - Abdul Syahid; Yeni Suryani; Lafifah Suliyya; Fatma; Winna (Journal of English for Specific Purposes in Indonesia, 2024)
The development of English language proficiency for specific purposes (ESP) plays an important role in preparing learners for success in an increasingly globalized work environment, particularly in the field of business. In this context, the evaluation of ESP textbooks, such as "Intelligent Business”, the critical evaluation of English teaching materials, particularly focusing on the textbook "Intelligent Business" within the realm of English for Specific Purposes (ESP). The assessment is based on Cunningsworth's (1984) criteria, emphasizing aspects such as content relevance, organization, language presentation, and activities. The textbook is scrutinized for its effectiveness in enhancing business English skills, with a particular emphasis on vocabulary, grammar, and skill development, and sheds light on the collaborative efforts and acknowledgments involved in creating the coursebook, underscoring its value as a learning resource. Through this evaluation, the study aims to provide insights into the suitability and efficacy of the textbook in facilitating language learning in a business context. The data collection technique used is a documentation study by analyzing the textbook based on those evaluation criteria. It is expected that the results of the analysis can provide in-depth insight into the strengths and weaknesses of this textbook and provide guidance for the development of more effective textbooks in the context of ESP learning in the field of business. By focusing on the evaluation of ESP textbooks in the business context, this study is expected to make a significant contribution to the development of English language teaching and learning practices for specific purposes in various business environments.